Female urinary incontinence (Portuguese Journal of Family Medicine and General Practice, 2005)
Introduction: Urinary incontinence (UI) is a health problem with important consequences. It has a high prevalence in adult women.Despite this, only one third of the patients inform their doctor of their UI. This problem has not been very well studied in Portugal. Objectives: To determine UI prevalence, its characteristics and treatment expectations in women 40 or older. To determine the percentage that reported UI to their doctor and the reasons for not reporting. To establish the association between UI type, its gravity and age. To identify the explanatory factors for reporting UI to the doctor. Study type: Observational, cross-sectional, descriptive with analytic component. Setting: Senhora da Hora Health Centre, Portugal. Population: Women 40 or older, registered at the Sa da Hora Health Centre. Methods: Random sample of 400 women 40 years old or older registered at Senhora da Hora Health Centre. A self-questionnaire was applied. Statistic analysis: sample description, 2 test (compare ratio), logistic regression (explanatory factors for reporting UI). Results: Response rate: 71,75%. The prevalence of UI reached 35,2%. 59% of the incontinent women consider this problem as being very important. Only 34,2% report their problem to the doctor and the most frequent reasons not to communicate it were to consider it a normal event, part of ageing (25%) or to think that it would disappear without help (23%). The explanatory factors for reporting UI to the doctor were the quantity and the duration of the urine loss. Discussion/Conclusion: The UI prevalence in women is high. Only one third talked with the doctor about this problem. New studies are needed to evaluate the knowledge about UI and its treatment and to modify the behaviour of the patients/doctors in face of this problem.
Keywords: Urinary Incontinence; Prevalence; Healthcare-seeking Behaviour; Female